\(Q=\frac{2^{12}.3^5-4^6.81}{\left(2^2.3\right)^6+8^4.3^5}=\frac{2^{12}.3^5-2^{12}.3^4}{2^{12}.3^6+2^{12}.3^5}\)
\(=\frac{2^{12}.3^4.\left(3-1\right)}{2^{12}.3^5.\left(3+1\right)}=\frac{2}{3.4}=\frac{1}{6}\)
Q = \(\frac{2^{12}.3^5-4^6.81}{\left(2^2.3\right)^6+8^4.3^5}\)
= \(\frac{2^{12}.3^5-2^{12}.3^4}{2^{12}.3^6+2^{12}.3^5}\)
= \(\frac{2^{12}.3^4.\left(3-1\right)}{2^{12}.3^5.\left(3+1\right)}\)
= \(\frac{2}{3.4}=\frac{1}{6}\)
\(Q=\frac{2^{12}\cdot3^5-4^6\cdot81}{\left(2^2\cdot3\right)^6+8^4\cdot3^5}\)
\(Q=\frac{2^{12}\cdot3^5-\left(2^2\right)^6\cdot3^4}{2^{12}\cdot3^6+\left(2^3\right)^4\cdot3^5}\)
\(Q=\frac{2^{12}\cdot3^5-2^{12}\cdot3^4}{2^{12}\cdot3^6+2^{12}\cdot3^5}\)
\(Q=\frac{2^{12}\cdot\left(3^5-3^4\right)}{2^{12}\cdot\left(3^6+3^5\right)}\)
\(Q=\frac{3^5-3^4}{3^6+3^5}\)
\(Q=\frac{162}{972}\)
\(Q=\frac{81}{486}\)
\(Q=\frac{1}{6}\)